2008
DOI: 10.1016/j.jaridenv.2007.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Fifty years of landscape evolution in Southwestern Mauritania by means of aerial photos

Abstract: South-western Mauritania is located in a semi-arid environment exposed to large rainfall variations and affected by a severe drought since the mid-1960s. The studied area includes the right bank of the Senegal River and the southern extension of the Saharan sandy dunes and is based on the analysis of climatic data, field studies, and four aerial surveys realized since 1954.The climatic analysis shows that, after a strong decline of yearly rainfall started in the mid-1960s, a significant increase is observed fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 15 publications
5
19
0
Order By: Relevance
“…These results may show sign towards a progressive return on more favorable rainfall conditions as mentioned by Ozer et al (2003). These results confirmed those of some authors (Ozer et al, 2003 ;Niang et al, 2008 ;Hountondji et al, 2009 ;Ozer et al, 2009 ;Ouoba, 2013 ;Panthou et al, 2014) who suggested a return of wetted period since the 1990s. However, they contrasted the findings of several other authors (L'hote et al, 2002 ;Frappart et al, 2009 ;Lebel et Ali, 2009).…”
Section: Trend Analysissupporting
confidence: 88%
“…These results may show sign towards a progressive return on more favorable rainfall conditions as mentioned by Ozer et al (2003). These results confirmed those of some authors (Ozer et al, 2003 ;Niang et al, 2008 ;Hountondji et al, 2009 ;Ozer et al, 2009 ;Ouoba, 2013 ;Panthou et al, 2014) who suggested a return of wetted period since the 1990s. However, they contrasted the findings of several other authors (L'hote et al, 2002 ;Frappart et al, 2009 ;Lebel et Ali, 2009).…”
Section: Trend Analysissupporting
confidence: 88%
“…On the other hand, research showed no decrease in tree density at sites in Burkina Faso (Rasmussen et al, 2001), Mali (Hiernaux et al, 2009), and the Republic of the Sudan (Schlesinger and Gramenopoulos, 1996). Agricultural expansion and livestock grazing, not climate, reduced tree density at sites in Mauritania (Niang et al, 2008) and Senegal (Lericollais, 1989). Recent natural regeneration by farmers increased tree density at a site in Burkina Faso (Reij et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The harshness of the desert, low probability of finding prey and high risk of dehydration certainly affect survival of migrating birds. This is aggravated by strong winds, creating dust storms which have dramatically increased in frequency since the late 1950s (Goudie & Middleton 2006;Niang et al 2008). In order to investigate possible difficulties and hazards for avian migrants crossing this geographical barrier, we have evaluated migratory journeys across the Sahara Desert made by raptors recorded by satellite telemetry.…”
Section: Introductionmentioning
confidence: 99%